Effects of naringin on physical fatigue and serum MMP-9 concentration in female rats - Mohammad Zamanian; Mohammadreza Hajizadeh; Ali Shamsizadeh; Mohammad Moemenzadeh; Morteza Amirteimouri; Mohammad Elshiekh; Mohammad Allahtavakoli (Taylor & Francis Group, 2017)
Context: Oxidative stress has a critical role in the development of physical fatigue and activation of matrix metalloproteinases-9 (MMP-9). Naringin (Nar) is a bioflavonoid that has antioxidant activity and suppresses MMP-9 expression. Objective: The present study evaluates the anti-fatigue activity of Nar on physical fatigue and serum MMP-9 concentration in rats. Materials and methods: Fifty female Wistar rats were randomly divided into five groups (n = 10); a control group, vehicle group and three Nar treatment groups. The Nar treated groups received different doses of Nar (40, 80 and 160 mg/kg/day) for 30 days. On the 30th day, rats were sacrificed immediately after exhaustive swimming test. Serum MMP-9 concentration and several biochemical parameters related to fatigue were measured. Results: Exhaustive swimming time in the Nar-80 group significantly increased 1.78-, 1.53-, 1.5- and 1.3-fold compared with the control, vehicle, Nar-40 and Nar-160 groups, respectively. In addition, exhaustive swimming time in the Nar-160 group significantly increased 1.36-fold compared with the control group. Nar-80 significantly decreased LDH activity by 60.45% and 57.47% compared with the vehicle and control groups, respectively. Furthermore, Nar-80 and Nar-160 increased blood glucose levels by 19.56% and 18.38% compared with the control group, respectively. Nar-80 and Nar-160 significantly decreased serum MMP-9 concentration by 61.57% and 83.39% compared with the control group, respectively. Conclusion: Based on our data, Nar has anti-fatigue effects which may be attributed to its property in modulating energy metabolism and reducing serum MMP-9 concentration. Thus, Nar may be a promising agent for the treatment of physical fatigue.